HUBUNGAN ANTARA MANAJEMEN PEMELIHARAAN DENGAN KEMAMPUAN MENGAWINI PADA KUDA PEJANTAN DI TOMBO ATI STABLE SALATIGA, JAWA TENGAH - , SRI LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job Training Activity in Tombo Ati Stable on March 24 to 29, 2014 is determined to know the maintenance management of horses. Tombo Ati Stable is located in Buluh, Tengaran, Semarang, Central Java. Writing the final paper aims to determine the maintenance management that related to the stud fertility and the ability to marry which served as stallion for breeding in Tombo Ati Stable. The daily activities at Tombo Ati Stable included feeding and drinking water, cleaned the cage area, horse grooming, horse exercise, horse teasing, horse mating, and other specific activities. Data collection methods included some direct observation or observation which worked together and followed the daily activities at Tombo Ati Stable , interviewed to the owner, the employee or person in charge of the farm and medic, as well as from the ownerâs record and the image objects. The stud feeding in Tombo Ati Stable was in conformity with the requirements. The stud daily care and health have been well and regularly implemented. Horse mating procedures are also highly considered in order to minimize the cases of transmission disease, injury, or even failure pregnancy. Tombo Ati Stable has good maintenance management, it have been seeing from the studs which Hanoman YR, Pitu Likur, and Bayu Menoreh that all of them have great libido and copulatory behavior, it has showed that the studs of Tombo Ati Stable have a high fertility and absence of the illness cases.